Drought-Conditioning of Quaking Aspen (Populus tremuloides Michx.) Seedlings During Nursery Production Modifies Seedling Anatomy and Physiology - Sloan, Joshua L.; Burney, Owen T.; Pinto, Jeremiah R. (Frontiers in Plant Science, 2020)
In the western US, quaking aspen (Populus tremuloides Michx.) regenerates primarily by root suckers after disturbances such as low to moderate severity fires. Planting aspen seedlings grown from seed may provide a mechanism to improve restoration success and genetic diversity on severely disturbed sites. However, few studies have examined the use of container-grown aspen seedlings for restoration purposes from both the outplanting and nursery production perspective. Thus, the purpose of this novel study was to examine how alterations in irrigation levels during nursery production across three seed sources would impact seedling performance attributes on harsh, dry outplanting sites. Irrigation treatments were based on three irrigation levels, determined gravimetrically: High = 90%, Medium = 80%, and Low = 70% of container capacity. The three seed sources represented a latitudinal gradient across the aspen range (New Mexico, Utah, and Alberta). Carbon isotope analysis indicated irrigation treatments were effective in creating higher levels of water stress for both the Low and Medium irrigation levels compared to seedlings under the High irrigation level. Seedlings subject to the Low irrigation level were found to induce greater height, higher photosynthetic rates, larger percentages of hydraulically active xylem, and faster xylem flow velocities compared to the High irrigation level. The lack of an interaction between irrigation treatments and seed source for nearly all response variables suggests that nursery conditioning via irrigation limitations may be effective for a range of aspen seed sources.